Transnational parenting from the views of fathers: a study on Nepalese immigrants living in Portugal - Pant, Ritu (2021)
This study discusses the experiences and perceptions of Nepali transnational fathers who are practicing or have practiced parenting from distance in Lisbon, Portugal. It explores their migration trajectories, transnational parenting experiences before reunification (if already united with children) and their family reunification plans (of those who are yet to be united with their children). Symbolic interaction theory provides basis of analysis, which is supported by theoretical concepts on transnational parenting. The eight participants of this qualitative study were selected by non-probability sampling using snowballing technique. Most in-depth interviews were taken online due to the Covid-19 pandemic situation. Thematic analysis was employed to categorize the findings into themes and sub-themes. According to the study’s findings, Nepalese travel to Portugal with aim of bringing their families to settle in Europe. Despite many family reunification requirements set out by the Portuguese immigration policies, Nepalese migrants perceive Portugal as flexible gateway to enter Europe and invite their families. Furthermore, available social networks allowed the migrants to sustain their lives and get jobs after moving to Portugal, which encouraged them to plan family reunification. In terms of transnational parenting practices, regular communication and sending of remittances helped Nepali fathers to maintain transnational ties with their families at home. Significantly, social interaction with different relations influenced their perception on fathering and parenting practices.